Foetal Limb in Bladder: A rare complication of vesicouterine fistula (Indian Journal of Case Reports, 2022)
Vesicouterine fistula(VUF) is a rare urogenital fistula and more rarer is the pregnancy in its presence. Even if pregnancy occurs the outcomes appears to be very poor .Most of the cases are related to iatrogenic bladder injury during caesarean section. There is very limited literature on the pregnancy with VUF associated with herniation of foetus or foetal part(s) into the bladder cavity. Here we report a case of pregnancy in a known case of untreated VUF. She presented at 23 weeks of gestation with features of premature rupture of membrane and herniation of foetal left lower limb inside the bladder cavity. Her pregnancy ended up with hysterotomy and removal of non-viable foetus along with fistula repair. So, regardless of the severity of the signs and symptoms associated with VUF clinicians should convince the patients for repair of the fistula especially if future pregnancy is contemplated .